16 Management of tricuspid valve regurgitation in congenital heart disease: a single centre experience. (17th July 2020) - Caroli, Silvia; Parry, Helen; English, Kate
Abstract : Background: Congenital anomalies of the tricuspid valve (TV), pose significant management challenges; when to intervene, what type of repair should be performed and when is TV replacement preferable. This observational study documents outcomes following TV repair versus replacement in a single centre. Methods: A total of 73 patients underwent tricuspid valve surgery in our centre from January 2014 to November 2019. Patients with primary left heart lesions, AVSD repair or systemic right ventricle (RV) were excluded. The final study population included 57 patients. Ebstein anomaly was present in 16 patients (28%) and previous Tetralogy of Fallot repair in 12 patients (21%). Echocardiographic assessment of the degree of TV regurgitation pre and post-surgery and degree of RV dysfunction, was visually performed by a single operator accredited in congenital echocardiography (SC). Results: TV replacement was performed in 12 patients (21%) and TV repair in 45 patients (79%). One patient with Ebstein anomaly initially underwent TV repair but required TV replacement one year later. The mean age was 46 ± 13.5 year in patients undergoing replacement and 33 ± 14 year in patient undergoing TV repair (p= 0.0081). The mean body mass index (BMI) in the TV replacement group was 29.9 ± 4.9 vs 23.8 ± 4 in the repair group (p=0.0037). Overall 30-day mortality was 1.7% due to the death of a patient with severe Ebstein anomaly undergoing TV replacement who died on ECMO two weeks post-operatively. Most patients (91%) who underwent TV replacement had a degree of RV impairment pre-operatively compared to the 29% of patients undergoing TV repair. All the patients with severe RV dysfunction post TV replacement had at least moderate RV dysfunction pre-operatively. Severe TR was present in 8 (66%) of the patients undergoing TV replacement and 20 (45%) who underwent TV repair. Three patients (25%) post TV replacement required re-admission for signs of RV failure compared to 1 (2%) in the TV repair group. Discussion: Our data, in line with previous series, suggest patients undergoing TV repair have better outcomes compared to TV replacement, with lower mortality and re-admission with RV failure. Patients undergoing TV replacement were significantly older with higher body mass index than patients undergoing TV repair. It is likely these factors influenced decision making; greater peri-operative risk is associated with prolonged bypass time; bypass time is generally prolonged in TV repair relative to replacement. Older patients with raised body mass index may have been deemed too high peri-operative risk to undergo repair. Alternatively, it may be that delaying intervention in TV disease technically makes repair more challenging. This poses the questions whether outcomes would be better if intervention were performed earlier in TV disease and if we focused on optimising patients' pre-operative fitness prior to surgery. We recognise this observational, retrospective study with small sample size has its limitation. A more reliable assessment of the RV function through TDI and TAPSE would be preferable together with a larger study population to validate these findings. Conclusions: Patients outcomes were better following TV repair compare to replacement. Patients who underwent TV replacement tended to be older and with higher BMI posing the questions whether we should intervene earlier and optimise patients' fitness prior to surgery. Conflict of Interest: None